The diagnostic approach to fine‐needle aspiration of malignant lymphoma: Using cytomorphology and immunocytochemistry with cell transfer method. Issue 8 (18th February 2014) - Oh, Eun Ji; Hong, Soon Won; Jeong, Hyeong‐Jae; Yoon, Sun Och
<x xml:space="preserve">Abstract</x> Fine‐needle aspiration (FNA) cytology is generally considered to be the screening tool for lymphoproliferative lesions. The differential and decisive diagnosis, however, of malignant lymphoma from benign reactive hyperplasia by FNA cytology is sometimes challenging. The diagnostic features compatible with lymphoma as opposed to reactive hyperplasia in FNA cytology were investigated with 31 cases of lymphoma and 31 cases of reactive hyperplasia, and immunocytochemistry with cell transfer method was additionally applied to FNA cytology. The predominance of large lymphocytes, the clustering of large lymphocytes, the presence of markedly large and/or highly pleomorphic cells, the presence of apoptotic and/or necrotic cell debris were considered characteristics of lymphomas, whereas the predominance of small lymphocytes and the presence of histiocytes were considered characteristics of reactive hyperplasia. Using these cytomorphologic characteristics, the diagnostic accuracy for malignant lymphoma in FNA cytology had a sensitivity of 80.6% and a specificity of 100%. By cell transfer method, one of Papanicolaou‐stained slides could be used in immunocytochemistry for several markers. Using such methods, sensitivity of FNA cytology for lymphoma was upgraded to 100%, and decisive diagnoses of diffuse large B‐cell lymphoma, Burkitt lymphoma, low grade B‐cell lymphoma, T‐ or NK‐cell non‐Hodgkin lymphoma (NHL), or Hodgkin lymphoma was possible. Differential diagnosis of malignant lymphoma from reactive hyperplasia, and decisive diagnoses of high, and low grade B‐cell NHL, T‐ or NK‐cell NHL, and HL could be possible by FNA cytology with cytomorphology in conjunction with immunocytochemistry using cell transfer method. Diagn. Cytopathol. 2014;42:671–679. © 2014 Wiley Periodicals, Inc.